Self-help Development for Welfare Provision, the People Inputs in Participation - Natal Martínez, Alejandro (CIENCIA ergo-sum, 2017)
The present paper is about people 's participation the provision of service of poverty relief. It presents some preliminary conclusions of the first year of research activities within the project "Participación Popular en el Desarrollo Social" ("People's Participation in Social Development") currently being carried out at the Centro de Investigación en Ciencia Política y Administración Pública of the "Facultad de Ciencias Políticas y Administración Pública of the UAEM.  As part of a large research project, the paper focuses on the study of self-help organizations. lt analyses the fate of self-help organisations after they are considered as having reached "maturity", i. e. as being capable of developing without the interference of an outside agent. An attempt is made to assess the development of self-help organisations after withdrawal of the outside agent (NGOs or government agencies), and the implications of this development for community development, specifically in terms of service provision for poverty relief. The research project is based principally on E. Ostrom and E. A. Brett's work on institutional design for assessing the institutional framework and the sociodynamics of choice for service provision, i. e. why and how people chose to participate in the provision of service.